فقه السياسة المالية في عهد عمر بن عبد العزيز: دراسة مقاصدية في ضوء الواقع المعاصر (بيت المال في ولاية سلانجور أنموذجا) - Umaimah Mohammed (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The research presents a study in the jurisprudence of financial policy under the reign of Caliph Umar bin 'Abd al-Aziz, in the light of contemporary reality. The research chose Malaysia as a model for contemporary study. The Research hope to develop the objectives of the Maqasid al-Shari'ah via the evaluation of Islamic Jurisprudence data and its implementation in the Baitul al-Mal of Malaysia in the context of contemporary fiscal policy. The research was based on the inductive method by collecting data and information as regard to the financial policy, methodology, analytical approach in the analysis of the financial policy of Umar bin 'Abd al-Aziz, the opinion of the Islamics scholars and the related judgment as regard to the era of Umar bin 'Abd al-Aziz in benefitting it for the Baitul al-Mal of Malaysia. On top of that, the research also took the historical approach by collecting the historical information related to its financial policy. This research has covered and reviewed various topics within the compound of financial policy, its concept, the principles, the legal maxim in the fiscal policy of Umar bin 'Abd al-Aziz and the potential of implementing it in Malaysia environment. This research has concluded that the Baitul al-Mal is one of the most important Islamic financial institutions to achieve the objective of the Maqasid al-Shari'ah. The idea of tax elimination is one of the most important means in helping the Ummah to achieve one of the objectives of Maqasid al-Shari'ah i.e. the protection of wealth. Furthermore, the investment by Baitul al-Mal will spur the economy of Malaysia and to achieve another objective of Maqasid al-Shari'ah i.e. the protection of life through the provision of employment for the Ummah.